Finding home in online community: exploring TikTok as a support for gender and sexual minority youth throughout COVID-19 - Hiebert, Alexa; Kortes-Miller, Kathy (Journal of LGBT youth, 2023)
In March 2020, with the global number of COVID-19 cases on the rise, many people were advised to stay at home and leave only for necessities. Across the globe, people were on lockdown. Very little is known about how this period of quarantine due to the pandemic has impacted the lives of gender and sexual minority youth. Between February and June of 2020, TikTok-a short- video sharing platform-was the most downloaded social media app. The purpose of this study was to use a digital ethnographic approach on TikTok to explore the experiences of gender and sexual minority youth during COVID-19. Thematic analysis of the data collected resulted in an overarching theme of TikTok as a supportive community. Additionally, four sub themes were examined including support with family relationships, identity formation, community and belonging and sharing knowledge and information. This study demonstrates the need for further research into gender and sexual minority youth social media cultures and highlights the resilience and resourcefulness of gender and sexual minority youth when faced with unprecedented circumstances.